The hyper order and fixed points of solutions of linear differential equations - Lianzhong Yang; Nan Li (Electronic Journal of Qualitative Theory of Differential Equations, 2013)
In this paper, we obtain a precise estimation of the hyper order of solutions for a class of higher order linear differential equation, and also investigate the exponents of convergence of the fixed points of solutions and their first derivatives for the second order case. These results generalize the results of Gundersen-Steinbart, Wittich and Chen-Shon.